Application of 5G to current differential protection of distribution network - Yuxiang LV; Yang YANG; Yawen DONG; Yucheng WANG (Dianxin kexue)
Driven by the strategy of grid as a Platform,Hub,and Sharing as well as the construction of Energy Internet and Ubiquitous power Internet of Things declared by Sate Grid Corporation of China,the intelligent distribution network evolves towards Distribution Internet of Things in a gridding and multi-source manner.The traditional distribution network protection and feeder automation barely meets the self-healing requirements of a strong distribution network.The current differential protection is prevailing due to its favorable quick-acting,sensitivity and selectivity.The existing communication solutions baring protection signals includes:fiber channel,230MHz/1.8GHz private wireless network,etc.However,the above methods are usually costly and perhaps with poor stability and low real-time performance.An realistic baring scheme for current differential protection of distribution network over the fifth generation communication system (5G) was proposed,where the of sampling data transmission between differential protection devices was realized based on 5G new radio technology.Thanks to the advantages of low latency,high capacity,security,etc.,5G-based differential protection can dynamically adjust the configuration to accommodate the topology changes,and thus can reduce the transformation and maintenance cost of distribution network.